A perspectiva do designer sobre a busca por informações do usuário no desenvolvimento de projeto de produto - Schmidt, Júlia Taiana (Universidade do Vale do Rio dos Sinos, 2016)
Design focus has shifted from the technical object to the human. Therefore, developing a new product demands user knowledge in several aspects. Deepening those aspects implies in searching for specific informations and demands research, analysis and, consequently, time and financial investment. However, the design practice is almost always developed with limited time and money, what implies that user participation is not always a priority. The main purpose of this dissertation is to comprehend how designers search for user information and data in product design. For this, individual interviews were conducted with professional designers awarded in the “4º Prêmio Bornancini de Design 2012” and “5º Prêmio Bornancini de Design 2014”. The data obtained were analyzed using the content analysis technique. It was perceived that the choice of the method used by the designers to understand the user is conditioned by external factors, that technology supports and modifies the methods used; and that the data collected in the researches serve as evidences in the negotiation process. Besides, there seems to be a lack of clarity on the structure of the methods related to the project process, and that the information designers research usually responds to technical interests. In this way, it is concluded that there are many particularities in the user information research process that are not contemplated in the literature.
Keywords: Design; Usuário; Métodos; Pesquisa de usuário; Design de produto; User; Methods; User research; Product design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial